BUSINESS FEASIBILITY ANALYSIS OF HAND LINE TUNA SHIP >30 GT (PAMO SHIP) AT BITUNG OCEAN FISHING PORT, NORTH SULAWESI, INDONESIA - Darondo F.A.; Putri E.T.; Krisnafi Y.; Fadly Z.R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Bitung City is one of the centers of fishing industry activity with a very strategic location. Yellowfin tuna is the dominant species of tuna which is always caught throughout the year which is landed at the Bitung Ocean Fishing Port using hand line tuna fishing gear. This research was carried out with the aim of knowing the costs, revenues and profits, the balance value of revenues and costs (R/C ratio), the Break Even Point (BEP) of hand line tuna fishing businesses with vessels > 30 GT. This research uses descriptive quantitative and qualitative methods. Primary data and secondary data were obtained through interviews and direct observation. The results showed that the total costs in the tuna hand line business amounted to 95,509.2 USD/year, revenues of 191,018.4 USD/year and the average profit earned was 103,149.94 USD/year. The results of the Reveneu Cost Ratio (R/C ratio) analysis are 2.0 so that the tuna hand line business is categorized as feasible and profitable. The results of the Break Event Point (BEP) analysis of the tuna hand line business were achieved at a total production of 7,368 kg or a selling price of 41,785.28 USD for tuna. Payback Period (PP) analysis results are 1.4 (1 year 4 months or 8 trips).